An Au(111)-dominant polycrystalline gold/gold nanoparticles/1, 8-naphthyridine/glassy carbon electrode for anodic stripping voltammetry determination of As(III). (1st October 2022) - Ye, Meng-Hua; Chen, Jun-Rong; Sun, Han-Zhou; Xiao, Hong-Bo; Yang, Ting; Wang, Wen-Lei; Xie, Qing-Ji
Abstract: We report the fabrication of a 1, 8-naphthyridine (Naph), gold nanoparticles and then Au(111)-dominant polycrystalline gold (Au(111)dpg ) modified glassy carbon electrode (GCE) for linear sweep anodic stripping voltammetry (LSASV) determination of As(III). An ultrathin film of Naph was chemically bonded on a GCE by electroreduction of Naph in acidic solution. The bipyridine group of Naph on the Naph/GCE can capture gold nanoparticles (AuNPs) by coordination adsorption and can then direct an Au(111) oriented crystalline growth during gold staining in HAuCl4 –NH2 OH solution, due to the different affinities of Au(110), Au(100) and Au(111) facets to the pyridine unit in Naph. The prepared Au(111)dpg /AuNPs/Naph/GCE and the control electrodes were characterized by electrochemical methods, X-ray photoelectron spectroscopy, X-ray diffraction and scanning electron microcopy. LSASV determination of As(III) was performed on the Au(111)dpg /AuNPs/Naph/GCE with high performance. Sensitivity values of 11.6 µA ppb –1 (2.3∼75 ppb) and 3.1 µA ppb –1 (2.3∼75 ppb), as well as limit of detection values of 0.15 ppb and 0.52 ppb (S/ N = 3) were obtained on the basis of the LSASV oxidation signals of As(0)→As(III) and As(III)→As(V), respectively. The Au(111)dpg /AuNPs/Naph/GCE was applied for As(III) determination in river water samples with satisfied results.